Cis-acting elements and trans-acting factors for accurate translation of chloroplast psbA mRNAs: development of an in vitro translation system from tobacco chloroplasts. - Hirose, T (1996)
Translational regulation is an important step of gene expression in chloroplasts. To analyze biochemical mechanisms of translational regulation unique to higher plant chloroplasts, an in vitro translation system has been developed from tobacco chloroplasts. Conditions for chloroplast extraction and the in vitro translation reaction have been optimized with a tobacco psbA-lacZ fusion mRNA. The in vitro system supports accurate translation of a variety of chloroplasts mRNAs. Using a series of mutant psbA mRNAs, we showed that three elements within the 5'-untranslated region of the mRNA are required for translation. Two of them are complementary to the 3'-terminus of chloroplast 16S rRNA (termed RBS1 and RBS2) and the other is an AU-rich sequence (UAAAUAAA) located between RBS1 and RBS2 and is termed the AU box. mRNA competition experiments using the in vitro translation reaction and gel mobility shift assays revealed the existence of a trans-acting factor(s) for translation and its possible interaction with the AU box. We propose a model for the initiation of psbA translation whereby RBS1 and RBS2 bind cooperatively to the 3'-end of 16S rRNA resulting in looping out of the AU box, which facilitates the interaction of a trans-acting factor(s).